SPE/IADC Drilling Conference 1989
DOI: 10.2118/18637-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Natural Gas Hydrates in Various Drilling Fluids

Abstract: SPE Members Abstract This paper presents laboratory-derived equilibrium temperature and pressure data for gas hydrates in drilling fluids. Data are included for lime sea-water gypt polymer and dispersed muds with varying salt polymer and dispersed muds with varying salt concentrations, as well as several experimental fluids. Equilibrium curves to determine salt requirements in deep-water drilling muds also are included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The study found that salt and montmorillonite are the predominant factors influencing the phase equilibrium and formation of natural gas hydrates. Building upon this, Lai et al [12] increased the pressure to 28.96 MPa and conducted experiments on 16 simulated drilling fluids. The results indicated that both salt and isopropanol could inhibit the formation of hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that salt and montmorillonite are the predominant factors influencing the phase equilibrium and formation of natural gas hydrates. Building upon this, Lai et al [12] increased the pressure to 28.96 MPa and conducted experiments on 16 simulated drilling fluids. The results indicated that both salt and isopropanol could inhibit the formation of hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…A number of accidents suspected to be caused by hydrate in the mud during deepwater drilling operations were reported (Barker and Gomez , 1989). In laboratory scale the formation of hydrate in simulated drilling fluids was observed indicating that for many of the fluids studied, hydrates could be formed at relatively low pressures (< 2, 000 psig) (Lai and Dzialowski, 1989). The conventional response to drilling fluid formulation to inhibit gas hydrate formation in water-based drilling fluids has been the use of salts or combinations of salts with water-soluble organic compounds to decrease the likelihood of gas hydrate formation.…”
Section: Electrolytesmentioning
confidence: 99%